2017
DOI: 10.1128/aem.03098-16
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Evolution of Extreme Acidophile Sulfobacillus thermosulfidooxidans Potentially Driven by Horizontal Gene Transfer and Gene Loss

Abstract: Recent phylogenomic analysis has suggested that three strains isolated from different copper mine tailings around the world were taxonomically affiliated with Sulfobacillus thermosulfidooxidans. Here, we present a detailed investigation of their genomic features, particularly with respect to metabolic potentials and stress tolerance mechanisms. Comprehensive analysis of the Sulfobacillus genomes identified a core set of essential genes with specialized biological functions in the survival of acidophiles in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 97 publications
(137 reference statements)
3
38
0
1
Order By: Relevance
“…These extreme conditions induce selective pressures which have an impact on indigenous organisms, for example, the principal acidophilic organisms are autotrophic, able to use ferrous iron and reduced sulfur compounds as electron donors which are released from sulfide minerals during oxidative dissolution [ 8 ]. Apart from nutritional selection, it is plausible to hypothesize that genes from such organisms have also been genetically selected in order to improve the ability of the organism to survive under extreme conditions [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…These extreme conditions induce selective pressures which have an impact on indigenous organisms, for example, the principal acidophilic organisms are autotrophic, able to use ferrous iron and reduced sulfur compounds as electron donors which are released from sulfide minerals during oxidative dissolution [ 8 ]. Apart from nutritional selection, it is plausible to hypothesize that genes from such organisms have also been genetically selected in order to improve the ability of the organism to survive under extreme conditions [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…They are lost and gained more readily than core genes [ 25 – 27 ], and can endow their recipient with new traits that facilitate adaptation to a changing environment [ 28 , 29 ]. For example, the horizontal transfer of such genes has helped marine microbes adapt to a variety of carbon sources [ 19 , 30 ], it has helped bacteria adapt to extreme environments [ 31 , 32 ], and it has helped gut microbial communities or pathogens adapt to human hosts [ 33 , 34 ]. A recent comparative studies of 53 E. coli genomes showed that at least 10% of adaptations to new environments may have been achieved by horizontal gene transfer [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of next generation sequencing technologies accompanied with developing methodological and computational approaches has yielded valuable insights into the genetic traits of microorganisms in various habitats worldwide, such as their metabolic capabilities and evolutionary adaptation ( Cordero and Polz, 2014 ; Ji et al, 2014 ; Zhang and Sievert, 2014 ; Youssef et al, 2015 ; Zhang et al, 2016a , b , e , 2017a ). Plentiful genome data deluge in public databases have fueled the field of comparative genomics.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on bacterial genomes significantly expanded the scope of inter-species divergence ( Ullrich et al, 2016 ; Zhang et al, 2016e ). Also, intra-species differentiation has been observed based on individual genomes of certain species ( Zhang et al, 2016a , b , 2017a ). Spatial distance and environmental heterogeneity are recognized to be two major factors that contribute to genetic variation of microbial genomes and populations ( Ramette and Tiedje, 2007 ).…”
Section: Introductionmentioning
confidence: 99%